Peran Lembaga Dakwah Kampus Dalam Membina Akhlak Pada Mahasiswa Universitas Islam 45 - Sri Mulyani; Aulia Ayu Rohayah (Turabian: Jurnal Pendidikan Islam, 2024)
The purpose of this research is to determine the concept of morals and efforts to develop student morals at the Islamic University 45 Bekasi. This thesis was prepared based on field data using qualitative methods. The data collected was obtained through observation, in-depth interviews and documentation studies, while the analysis used qualitative descriptive analysis techniques, namely descriptions and descriptions of the collected data as a whole about an actual situation. The results of this research show that the campus da'wah institution at the Islamic University "45" Bekasi has a moral concept and makes efforts to develop and direct it. The concept of improving morals and efforts to improve them are closely related. In the concept of improving morals, LDK has 4 organized orders, namely (1) Preparing and improving individual abilities to do good deeds, (2) Preparing and improving participants' skills to do good deeds at the level of the da'wah movement , (3) Prepare and improve participants' skills to do charity at the community level, (4) Prepare and improve participants' skills to do charity and interact with non-Muslims. In line with the efforts that have been established by LDK in the form of a work program which includes three aspects, namely the spiritual/spiritual aspect, the fikriyah/intellectual aspect, and the physical/physical aspect (body resilience) as well as the muamalah/relationship aspect with fellow humans. Organizationally, LDK tends to be open (inclusive) but as a movement it tends to be exclusive. This is because it can be seen from several things, namely the distinctive appearance identity of LDK cadres (wide headscarves, Palestinian flags, not shaking hands with the opposite sex) and then the use of the hijab (barrier) in activities to provide distance in interacting with students outside UKM LDK.